SEARCH FOR SPINLESS BOSONS IN E+E- ANNIHILATION - Althoff, M; Braunschweig, W; Kirschfink, F; Martyn, H; Rosskamp, R; Schmitz, D; Siebke, H; Wallraff, W; Eisenmann, J; Fischer, H; Hartmann, H; Jocksch, A; et al. (1985)
We have measured the cross sections for e+e- → e+e-, e+e- → μ+μ-, e+e- → γγ and e+e- → hadrons in an energy scan at center of mass energies between 39.79 and 46.72 GeV in 30 MeV steps. New spinless bosons, whose existence has been postulated as a possible means to explain the anomalously large radiative width of the Z0 found at the CERN SPS pp collider, are ruled out in the scan region. The data are used to set limits on the couplings to lepton, photon and quark pairs of bosons with masses above 46.72 GeV. © 1985.